Архітектурні трактати в Польщі Нового часу - Ковальчик, Є. (Студії мистецтвознавчі, 2008)
The treatise of ancient Vitruvius was known in Poland at least starting from the mid-15th century. In modern times it was Italian architectural treatises that were popular – they combined theoretical deliberations with graphic patterns. The following treatises were the most popular: by Sebastian Serlio (in 7 books, published in 1537–1575), Vignola (1562), Palladio (1570). In the 17th century it was Vincenzo Scamozzi’s L’idea della architettura universale (1615) that was widely read; the author included the design of a fortified palace for Zbaraż in Volhynia commissioned by Krzysztof Zbaraski. During the Baroque an important role was played by Italian treatises: by Guarino Guarini (1686, 1737) and Andrea Pozzo (1693, 1700). In the 18th century Italian books had to rival French and German Musterbücher and treatises. The patterns were used by architects and builders for the designs of palaces, churches, portals, and tomb monuments. Books on architecture were to be found in the libraries of monarchs, magnates, higher clergy, rich nobility, and even the town patriciate.